The Synergism of 1-Methylcyclopropene and Ethephon Preserves Quality of “Laiyang” Pears With Recovery of Aroma Formation After Long-Term Cold Storage - Shu, Pan; Min, Dedong; Zhou, Jingxiang; Ai, Wen; Li, Jiaozhuo; Li, Zilong; Zhang, Xinhua; Shi, Zedong; Sun, Yingjie; Li, Fujun; Li, Xiaoan; Guo, Yanyin (Frontiers in Plant Science, 2020)
‘Laiyang’ pear is a climacteric fruit with a special taste and nutritional values but is prone to postharvest loss in aroma compounds and fruit quality. In this study, pears were pretreated with 0.5 μL L-1 1-methylcyclopropene (1-MCP) at 20 °C for 12 h and then stored at 0 ± 1 °C for 150 d to evaluate the influences of 1-MCP on fruit quality and the changes in components of volatile aromas. In addition, pears were further treated with 2 mmol L-1 ethephon. The effects of ethephon on the recovery of aroma production were investigated during the 150 d storage at 0 ± 1 °C and the subsequent 7 d shelf life at 20 ± 1 °C. The treatment with 1-MCP inhibited the firmness loss and the increase of electrical conductivity, reduced respiration and ethylene production rates as well as the contents of soluble solids, and maintained the storage quality of fruits. However, 1-MCP treatment inhibited the emission of volatile aromas in pear fruits by decreasing the activities of various enzymes, such as lipoxygenase (LOX), hydroperoxide lyase (HPL), alcohol dehydrogenase (ADH), pyruvate carboxylase (PDC) and alcohol acetyltransferase (AAT). During the shelf-life, the activities of the above enzymes were significantly enhanced and a higher content of volatile aromas were found in fruits treated with 1-MCP + ethephon while other qualities were not compromised. These results showed that 1-MCP treatment could effectively maintain the quality of ‘Laiyang’ pear during cold storage, and the additional application of ethephon on fruits during the shelf-life may be a promising way to restore volatile aromas in pear fruits after a long-term storage.